Inter-individual differences in the utilization of elastic energy during running affect the quadriceps femoris volume in highly trained/elite distance runners - Ando, R.; Ohnuma, H.; Tanji, F.; Ikeda, T.; Yamanaka, R.; Suzuki, Y. (Journal of Biomechanics, 2025)
The quadriceps femoris is larger in inferior distance runners than in superior distance runners within a cohort of competitive athletes (i.e., highly trained/elite runners). We hypothesize that distance runners who are less efficient at utilizing elastic energy during running show excessive hypertrophy of the quadriceps femoris. This study aimed to examine the relationship between thigh muscle size and indices of elastic energy utilization during running in highly trained/elite distance runners. Fifteen male distance runners (personal best time for 5000-m, 13'45"11 ± 19"91) participated. The volumes of the quadriceps femoris, hamstrings, and adductors were measured using magnetic resonance imaging and normalized to the participant`s body mass. The participants performed 60-m distance race-paced running and sprinting on an all-weather indoor track. Ground reaction force data were recorded and used to calculate vertical stiffness (kvert) and leg stiffness (kleg) as indices of elastic energy utilization. The kvert and kleg during distance race-paced running and sprinting were negatively correlated with the relative volume of the quadriceps femoris (r = -0.692 - -0.522, rs = -0.797, p < 0.05) but not with the hamstrings and adductors (r = -0.189-0.030, rs = -0.015 - 0.015, p > 0.05). In conclusion, highly trained/elite distance runners who are less efficient at utilizing elastic energy may accumulate more mechanical load on the quadriceps femoris during their daily running, which may be associated with a larger quadriceps femoris.